Evaluasi Kualitas Hidup Pasien Diabetes Mellitus Tipe 2 Dengan Kombinasi Anti Diabetik Oral-Oral Di RSUD Provinsi NTB - Baiq Lenysia Puspita Puspita Anjani; Nadia Sierly; Wirawan Adikusuma; Nurul Qiyaam; Nur Furqani; Cyntiya Rahmawati (Lumbung Farmasi: Jurnal Ilmu Kefarmasian, 2024)
Background: based on data from the Ministry of Health NTB, the prevalence of Diabetes Mellitus in West Nusa Tenggara in 2020 is around 59,606 people divided into 10 regencies and cities. The highest prevalence of diabetes is type 2 diabetes mellitus (DMT2). One way to assess the success of T2DM therapy is to measure quality of life using Quessionnair's Diabetic Quality Of Life Clinical Trial (DQLCTQ) questionnaire. The purpose of the study: to evaluate the quality of life of DMT2 patients who received oral-oral antidiabetic combination at West Nusa Tenggara Provincial Hospital. Method: observational  analytic with Cross Sectional design with  Concurrent patient data collection. Samples: 56 T2DM patients. The results of the study: on  the characteristics of respondents there was no difference in quality of life on gender, age, occupation and length of suffering from T2DM. Patients who received the combination of metformin and glimepiride had a quality of life score of 71.84, while patients who received the combination of metformin and glimepiride 74.77. Research conclusion: statistical test  with independent sample t-test showed no significant difference between the two groups (p = 0.268).